1988
DOI: 10.1021/j100319a042
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten disulfide: a novel hydrogen evolution catalyst for water decomposition

Abstract: Silica-supported tungsten disulfide was prepared by the reaction of W03/Si02 with H2S at 300 °C. The WS2 hexagonal structure was confirmed by X-ray diffraction analysis. AES and XPS studies show the existence of residual tungsten oxides in addition to WS2. Hydrogen evolution properties of WS2/Si02 were determined by catalytic and photocatalytic (in the presence of fluorescein or CdS as sensitizers) tests and by electrochemical measurements. These were compared with silica-supported platinum. Although a graphit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 5 publications
0
60
0
Order By: Relevance
“…Under irradiation and in the presence of photosensitizers, however, they show activity for hydrogen evolution. 14 decreased with a rise of calcination temperature. This effect was explained by a higher amount of structural defects on the surface, which are the catalytically active sites, for the samples annealed at a lower temperature.…”
Section: Mos 2 In Photocatalytic H 2 Evolutionmentioning
confidence: 92%
See 1 more Smart Citation
“…Under irradiation and in the presence of photosensitizers, however, they show activity for hydrogen evolution. 14 decreased with a rise of calcination temperature. This effect was explained by a higher amount of structural defects on the surface, which are the catalytically active sites, for the samples annealed at a lower temperature.…”
Section: Mos 2 In Photocatalytic H 2 Evolutionmentioning
confidence: 92%
“…9 In contrast, MoS 2 was for a long time not considered as a promising HER catalyst because bulk MoS 2 showed poor activity. [10][11][12][13][14] In 2005, Hinnemann et al reported that MoS 2 nanoparticles were active HER catalysts. 15 Since then, the interest in developing and using MoS 2 and related metal sulfides such as WS 2 as HER catalysts has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Nevertheless, very few studies have been conducted on WS 2 regarding to HER up to date. 5,9-11 The systematic studies of layered WS 2 materials for HER are still not available.…”
mentioning
confidence: 99%
“…[2][3][4] Tungsten disulfide, WS 2 , a member of the semiconducting transition metal dichalcogenide family, has drawn considerable attention due to its semiconducting nature and electrocatalytic activities. [5][6][7][8] Nevertheless, very few studies have been conducted on WS 2 regarding to HER up to date. 5,[9][10][11] The systematic studies of layered WS 2 materials for HER are still not available.…”
mentioning
confidence: 99%
“…This problem can be solved with metal sulfides, whose bandgaps are much smaller [37][38][39][40][41][42][43][44][45][46][47][48]. However, because sulfides undergo photocorrosion under bandgap irradiation [49][50][51], sacrificial electron donors, such as Na 2 S and Na 2 SO 3 [40,42], are necessary to maintain catalytic activity.…”
Section: Cdse Nanoribbons As a Quantum-confinedmentioning
confidence: 99%